2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32001
|View full text |Cite
|
Sign up to set email alerts
|

A Study of an Augmented Reality App for the Development of Spatial Reasoning Ability

Abstract: and then his M.S. and Ph.D. in Computer Science from the University of California, Berkeley. His research considered various user interfaces for humancomputer interaction among users with a wide range of technology skills. Bell later completed a post doc at UC Berkeley focused on teaching programming to non-computer science majors, and the development of spatial reasoning abilities for engineering students. Bell has worked at Michigan State University since 1995. His work focused on the development of K-12 tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The conclusion of previous study [31] confirms that the deployment of AR is possible to close the gender performance and retention gap in geography classes. Another research report showed that there was no significant difference in spatial thinking skills between male and female students [71].…”
Section: Issn: 2252-8822 mentioning
confidence: 94%
“…The conclusion of previous study [31] confirms that the deployment of AR is possible to close the gender performance and retention gap in geography classes. Another research report showed that there was no significant difference in spatial thinking skills between male and female students [71].…”
Section: Issn: 2252-8822 mentioning
confidence: 94%
“…Augmented reality and virtual reality (AR and VR, respectively) are growing technologies that allow users to visualize virtual or digital objects through a device such as a smart phone or headset [1]. For engineering educators, the motivation to develop AR content for their curriculum is most often in the pursuit of a tool that helps their students visualize abstract concepts [2][3][4] such as forces [5], molecules [6], electrical charges [7], and their impact on real systems. In a civil or mechanical engineering setting, AR shows promise as a tool to enable students to visualize force and moment vectors [8].…”
Section: Introductionmentioning
confidence: 99%